2012
DOI: 10.1371/journal.pone.0036186
|View full text |Cite
|
Sign up to set email alerts
|

Young HIV-Infected Children and Their Adult Caregivers Prefer Tablets to Syrup Antiretroviral Medications in Africa

Abstract: BackgroundProvision of anti-retroviral therapy (ART) for HIV-infected children is complicated using syrup formulations, which are costlier than tablets, harder to transport and store and difficult for health-workers to prescribe and caregivers to administer. Dispersible/crushable tablets may be more appropriate. We studied the acceptability of syrups and scored tablets among young children who used both in the AntiRetroviral Research fOr Watoto (ARROW) trial.MethodsARROW is an ongoing randomized trial of paedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 23 publications
3
28
1
Order By: Relevance
“…In contrast to our findings, a recent study in Zambia and Uganda found that parents/caregivers preferred pills over syrups for antiretroviral therapy for children above age 3 due to the number, weight, difficult transportation and conspicuousness of the bottles, though investigators did not explore the drawbacks of crushing solid formulations (reduced palatability, lower dosing accuracy, and pharmacokinetic changes) in depth [23].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, a recent study in Zambia and Uganda found that parents/caregivers preferred pills over syrups for antiretroviral therapy for children above age 3 due to the number, weight, difficult transportation and conspicuousness of the bottles, though investigators did not explore the drawbacks of crushing solid formulations (reduced palatability, lower dosing accuracy, and pharmacokinetic changes) in depth [23].…”
Section: Discussioncontrasting
confidence: 99%
“…For example, Yeung and Wong found that children with HIV as young as 3 years were prescribed stavudine as a solid dosage form. In a recent study in Uganda and Zimbabwe, 36% of children were able to swallow antiretroviral tablets intact (mean age 3.3 years), while 64% required them to be crushed or dispersed (mean age 2.9 years) …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, evidence has shown that children as young as 3 years old are able to swallow conventional tablets and capsules (Nahirya-Ntege et al, 2012, Kaplan et al, 2010, Czyzewski et al, 2000. On the other hand, older children and adolescents have reported swallowing difficulties, including as a barrier to adherence in chronic conditions (Hansen et al, 2008, Polaha et al, 2008, Hommel and Baldassano, 2010, Modi et al, 2013.…”
Section: Tablets and Capsulesmentioning
confidence: 99%